Respon Fisiologis Pasien Pasca Operasi Caesar Setelah Terapi Murotal Ar-Rahman - Wirakhmi, Ikit Netra; Hikmanti, Arlyana (Jurnal Keperawatan Soedirman, 2016)
Pain results in sympathetic stimulation, which leads to releasing of epinephrine, and affects in rapid heart rate, rapid and shallow breathing, increased artheries pressure. Selected drugs for pain promote side effects such as nausea, vomiting and dependence. A nonpharmacological such as reciting Quran is required. This study was to examine the effect listening recited Ar Rahmaan on physiological responses amongÃ‚Â  post section caesarean patients in dr. Goeteng Hospital. A quasy experimental study with Control Group pre-test and post-test desing was conducted. A consecutive sampling recruited 40 respondents divided into a control group (20) and treatment (20). The treatment group accepted standard therapy plus listening Ar Rahman murotal therapy for 13 minutes 55 seconds once. While the control group accepted standard therapy. Measurements conducted before and after the treatments. Changes of physical responses were analysed by Wilcoxon and Paired Samples t-test. Then, the differences in physiological responses changes and pain intensity between two groups were analysed Mann Whitney test.Ã‚Â  Results showed a significant differences in blood pressure between before and after treatment both in the control group and the treatment with p systoleÃ‚Â  0.003 and p diastole 0.018. However, there were no significant differences on the pulse rate and respiratory rate p (0.429 and 0,0666) respectively. It concluded that among post section cesarean patients murotal Ar Rahman decreased blood pressure but not it was not for pulse and respiratory rateÃ‚Â